Influence of Water Activity on Thermal Resistance of Microorganisms in Low‐Moisture Foods: A Review. Issue 2 (5th February 2016) - Syamaladevi, Roopesh M.; Tang, Juming; Villa‐Rojas, Rossana; Sablani, Shyam; Carter, Brady; Campbell, Gaylon
Abstract: A number of recent outbreaks related to pathogens in low‐moisture foods have created urgency for studies to understand the possible causes and identify potential treatments to improve low‐moisture food safety. Thermal processing holds the potential to eliminate pathogens such as Salmonella in low‐moisture foods. Water activity ( a w ) has been recognized as one of the primary factors influencing the thermal resistance of pathogens in low‐moisture foods. But most of the reported studies relate thermal resistance of pathogens to a w of low‐moisture foods at room temperature. Water activity is a thermodynamic property that varies significantly with temperature and the direction of variation is dependent on the product component. Accurate methods to determine a w at elevated temperatures are needed in related research activities and industrial operations. Adequate design of commercial thermal treatments to control target pathogens in low‐moisture products requires knowledge on how a w values change in different foods at elevated temperatures. This paper presents an overview of the factors influencing the thermal resistance of pathogens in low‐moisture foods. This review focuses on understanding the influence of water activity and its variation at thermal processing temperature on thermal resistance of pathogens in different low‐moisture matrices. It also discusses the research needs to relate thermal resistance of foodborne pathogens to a w value in those foods at elevated temperatures.